Differences in the Effect of Ankle Pumping and Kinesio Taping on Pitting Oedema in Hypertensive Patients - Juwita, Ade Lina; Wardhani, Riska Risty; Faidullah, Hilmi Zadah (FISIO MU: Physiotherapy Evidences, 2025)
Introduction: Hypertension is the first cause of death in the world and the fifth leading cause of death in Indonesia. The Special Region of Yogyakarta (DIY) ranks as the fourth province with the highest prevalence of hypertension. A consistent increase in blood pressure is known as hypertension. One method of controlling hypertension is the consumption of amlodipine, a drug that increases capillary hydrostatic pressure and functions as an antihypertensive agent. This study aims to determine the difference in the effect of ankle pumping and kinesio taping on piting oedema in hypertensive patients. Methods: This study is a quasi-experimental study with a pretest and posttest two group design. This study compares the treatment groups given ankle pumping and kinesio taping. Before treatment, both sample groups measured pitting oedema using a modified oedema ruler. Sampling in this study used purposive sampling technique. The data processing method in this study was descriptive analysis on age, body mass index (BMI), and pre and post pitting oedema values. Normality test using sahiro wilk test, hypothesis testing to test the difference between two groups using wilcoxon signed-ranks test and mann whitney test. Results: The results of pre and post values in groups 1 and 2 showed changes from degrees II and III down to degrees I and II. The sig value of p= 0.000 in ankle pumping exercises which means it can reduce piting oedema, for a p value = 0.083 which means that in the installation of kinesio taping there is no decrease in piting oedema. Conclusion: There is a difference in the effect of ankle pumping and kinesio taping on piting oedema in hypertensive patients.